2019
DOI: 10.1371/journal.pone.0214285
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early social deprivation on epigenetic statuses and adaptive behavior of young children: A study based on a cohort of institutionalized infants and toddlers

Abstract: Early social deprivation (i.e., an insufficiency or lack of parental care) has been identified as a significant adverse early experience that may affect multiple facets of child development and cause long-term outcomes in physical and mental health, cognition and behavior. Current research provides growing evidence that epigenetic reprogramming may be a mechanism modulating these effects of early adversities. This work aimed to investigate the impact of early institutionalization—the immersion in an extreme so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 92 publications
1
18
0
2
Order By: Relevance
“…Epigenetic mechanisms have been proposed to mediate the pernicious effects of the aforementioned environmental and sociodemographic risk factors. Genome-wide DNA methylation studies have revealed epigenetic patterns associated with socioeconomic status (Bush et al, 2018), institutionalization (Naumova et al, 2019), and altered stress reactivity after exposure to childhood maltreatment (Houtepen et al, 2016).…”
Section: Epigenetic Embedding Of Psychosocial Stressmentioning
confidence: 99%
“…Epigenetic mechanisms have been proposed to mediate the pernicious effects of the aforementioned environmental and sociodemographic risk factors. Genome-wide DNA methylation studies have revealed epigenetic patterns associated with socioeconomic status (Bush et al, 2018), institutionalization (Naumova et al, 2019), and altered stress reactivity after exposure to childhood maltreatment (Houtepen et al, 2016).…”
Section: Epigenetic Embedding Of Psychosocial Stressmentioning
confidence: 99%
“…Glucocorticoids may also play a role, as, in utero exposure to maternal under nutritional affects beta-cell number and function lifelong in a manner dependent upon GR and GC since deletion of the GR in foetal pancreatic cell abrogated this effect [ 3 ]. These changes may, in part be due to the effects of ELA on the methylation of genes involved in obesity and metabolic pathways [ 114 , 115 ]. Furthermore, adverse early life conditions induce lifelong changes in gene transcription [ 116 ].…”
Section: Early Life Adversitymentioning
confidence: 99%
“…Glucocorticoids may also play a role, as, in utero exposure to maternal under nutritional affects beta-cell number and function lifelong in a manner dependent upon GR and GC since deletion of the GR in foetal pancreatic cell abrogated this effect [3]. These changes may, in part be due to the effects of ELA on the methylation of genes involved in obesity and metabolic pathways [111,112]. Furthermore, adverse early life conditions induce lifelong changes in gene transcription [113].…”
Section: Early-life Adversity Diabetes and The Metabolic Syndromementioning
confidence: 99%